Consumer attitudes toward data breach notifications and loss of personal information - Ablon, Lillian (Research report (Rand Corporation), 2016)
"Data breaches continue to plague private-sector companies, nonprofit organizations, and government agencies. Despite the mounting rate of these breaches, the continuing harms imposed on consumers and firms, and over a decade of breach notification laws, very little research exists that examines consumer response to these developments. This report sets out the results of a nationally representative survey of the consumer experience with data breaches: the frequency of notifications of data breaches and the type of data taken; consumer attitudes toward data breaches, breach notifications, and company follow-on responses; and perceived personal costs resulting from the breach, with the goal to establish a baseline of information about consumer attitudes toward data loss and company practices in responding to such events. Key findings include: (1) Twenty-six percent of respondents, or an estimated 64 million U.S. adults, recalled a breach notification in the past 12 months; (2) 44 percent of those notified were already aware of the breach; (3) 62 percent of respondents accepted offers of free credit monitoring; (4) only 11 percent of respondents stopped dealing with the affected company following a breach; (5) 32 percent of respondents reported no costs of the breach and any inconvenience it garnered, while, among those reporting some cost, the median cost was 500 dollars; and (6) 77 percent of respondents were highly satisfied with the company's post-breach response"--Publisher's description